Chemoselective Hydrogenation Catalyzed by Pd on Spherical Carbon. Issue 12 (25th September 2013) - Esaki, Hiroyoshi; Hattori, Tomohiro; Tsubone, Aya; Mibayashi, Satoko; Sakata, Takao; Sawama, Yoshinari; Monguchi, Yasunari; Yasuda, Hidehiro; Nosaka, Kazuto; Sajiki, Hironao
Abstract We have developed a highly chemoselective hydrogenation method using a novel palladium catalyst supported on spherical carbon (0.5 % Pd/SC). The 0.5 % Pd/SC exhibited a novel catalytic activity and could achieve the chemoselective hydrogenation of alkynes, alkenes, azides, nitro groups, and aliphatic O‐tert‐butyldimethylsilyl (TBS) ethers without hydrogenolysis of benzyl esters, benzyl ethers, nitriles, aromatic ketones, N‐carbobenzyloxy (N‐Cbz) protective groups, and aromatic O‐TBS ethers.